Implementation of UPBJJ-UT Governance Policy Innovations Based on the Indonesian National Qualifications Framework in East Nusa Tenggara Province: Strategic Collaboration Approach Perspective - Agus Joko Purwanto; Rulinawaty; Setyo Kuncoro; Jasrial (International Journal of Science and Society, 2023)
Government policy in improving the quality of higher education and the quality of graduates through the Ministry of Research, Technology, and Higher Education's policies continues to experience significant development. One of the innovation policies for Higher Education governance is the realization of the Indonesian National Qualifications Framework (KKNI) which adapts to current developments in the current era of digitalization. This research seeks to see how the strategic collaboration approach is in developing the capacity of "quality UPBJJ-UT Governance Innovation based on KKNI" with the UPBJJ-UT analysis unit in East Nusa Tenggara. This research was carried out using a mixed method, where the methods used in this research were qualitative and quantitative. The results of the research gave birth to a recommendation model for the implementation of quality UPBJJ-UT Higher Education development policy innovations in East Nusa Tenggara Province.